1994
DOI: 10.1002/glia.440120109
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte and microglial motility in vitro is functionally dependent on the hyaluronan receptor RHAMM

Abstract: RHAMM (Receptor for Hyaluronic Acid Mediated Motility) has been identified as a receptor for the extracellular matrix component hyaluronan (HA) and was recently shown to be essential for the locomotion of normal and transformed peripheral cells. Until now the potential role of RHAMM in the motility of neural-derived cells has not been investigated. Here, we report that cultured primary astrocytes, astrocyte cell lines, and microglia express this receptor and exhibit RHAMM-dependent motility. Immunocytochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 71 publications
(97 reference statements)
1
30
0
3
Order By: Relevance
“…However, the immunolocalization data provide strong evidence that links the initial 12 h of increased motility following injury with the redistribution of RHAMM to the cell surface followed by its disappearance so that, by 18 h, only nuclear staining was observed. We have previously correlated rate of locomotion with cell surface localization of RHAMM in other cell types (27,43,44). The significance of the nuclear staining is unknown, but has previously been noted in fibroblasts (27).…”
Section: Discussionmentioning
confidence: 89%
“…However, the immunolocalization data provide strong evidence that links the initial 12 h of increased motility following injury with the redistribution of RHAMM to the cell surface followed by its disappearance so that, by 18 h, only nuclear staining was observed. We have previously correlated rate of locomotion with cell surface localization of RHAMM in other cell types (27,43,44). The significance of the nuclear staining is unknown, but has previously been noted in fibroblasts (27).…”
Section: Discussionmentioning
confidence: 89%
“…CD168, a RHAMM, has a dual function as an extracellular and an intracellular hyaluronan-binding-protein (25,26). Hyaluronan serves an important role in tissue organization and in cellular migration, growth and differentiation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies over the last several decades provide a connection between cell motility and HA [73][74][75][76][77]. One such study, comparing metastases and primary tumor staining, found that RHAMM expression was significantly higher in the metastatic cells.…”
Section: Receptor For Hyaluronic Acid Mediated Motilitymentioning
confidence: 99%